Examining Customer Engagement In Linking Social Media Content Quality, Influencer Credibility, And Purchase Intention - Sjaifudian, Hetifah; Sumarto, Siswanda H.; Husnah, Nuzul (Jurnal Ekonomi Syariah Pelita Bangsa, 2026)
This study examines the mediating role of customer engagement in the relationships between social media content quality, influencer credibility, and purchase intention toward MSME products in West Java. In digital marketing, platforms such as Instagram and TikTok have become important promotional channels for MSMEs, making content quality and influencer credibility key factors shaping consumer responses. This study used a quantitative approach with an explanatory research design. Data were collected through an online questionnaire from 200 respondents in West Java who actively use Instagram or TikTok, had seen MSME promotions in the last three months, and had been exposed to influencer-based promotions. Data were analyzed using Partial Least Squares Structural Equation Modeling. The results show that social media content quality and influencer credibility have positive and significant effects on customer engagement and purchase intention. Customer engagement also positively influences purchase intention and significantly mediates the effects of social media content quality and influencer credibility on purchase intention, indicating partial mediation. Social media content quality has the strongest effect on customer engagement, while influencer credibility has the strongest direct effect on purchase intention. These findings highlight the importance of content quality, credible influencers, and customer engagement in improving MSME marketing effectiveness.